2015
DOI: 10.4018/ijiit.2015010103
|View full text |Cite
|
Sign up to set email alerts
|

Filtering Structures for Microblogging Content

Abstract: In the last years, microblogging systems have encountered a large success. After 7 years of existence Twitter claims more than 271 million active accounts leading to 500 million tweets per day. Microblogging systems rely on the all-or-nothing paradigm: a user receives all the posts from an account s/he follows. A consequence for a user is the risk of flooding, i.e., the number of posts received from all the accounts s/he follows implies a time-consuming scan of her/his feed to find relevant updates that match … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…Groth et al (2010) analyzed the scientific discourse on the web using bibliometric techniques like citation and keyword similarity maps and concluded that scientific discourse on the web is contextually relevant. Dahimene and Mouza (2015) designed various filters to reduce the number of microblogs fetched by the system, while retrieving the users' relevant updates. Zhang et al (2013) identified the influential person in online social networks based on the tie strength.…”
Section: Influential Analysismentioning
confidence: 99%
“…Groth et al (2010) analyzed the scientific discourse on the web using bibliometric techniques like citation and keyword similarity maps and concluded that scientific discourse on the web is contextually relevant. Dahimene and Mouza (2015) designed various filters to reduce the number of microblogs fetched by the system, while retrieving the users' relevant updates. Zhang et al (2013) identified the influential person in online social networks based on the tie strength.…”
Section: Influential Analysismentioning
confidence: 99%